Final recommendations for the Latin America and Caribbean Periodontics Consensus 2024 - Cristina Cunha VILLAR; Paola CARVAJAL; Fernanda CARRER; Giuseppe Alexandre ROMITO; James Rudolph COLLINS; Marco Antonio ALARCÓN; Cassiano Kuchenbecker RÖSING; Juliano CAVAGNI; Andres Duque DUQUE; Gloria Inés LAFAURIE Villamil; Ricardo Guimarães FISCHER; Bernal STEWART; et al. (Brazilian Oral Research, 2025)
Abstract The 2024 Consensus on Periodontology for Latin America and the Caribbean addresses the significant public health issue of periodontal diseases, impacting millions in the region. This comprehensive document presents holistic recommendations to standardize diagnostic methodologies, enhance public awareness, and integrate preventive and therapeutic practices into general healthcare. Key areas include understanding the prevalence and impact of periodontal diseases, identifying risk factors, and improving diagnostic, preventive, and treatment strategies. The consensus emphasizes interdisciplinary collaboration, tailored public health interventions, and the importance of continuous monitoring and research. By unifying efforts across various sectors, the consensus aims to reduce the burden of periodontal diseases, thereby improving both oral and general health outcomes in Latin America and the Caribbean.